The Use of Construction Waste on Concrete Compressive Strength Using SNI 7656:2012 Method - E Rustiawandi1, R A Safitri (Jurnal Handasah, 2025)
Efforts to reduce construction waste and seek alternative construction materials have made the utilization of construction waste in concrete production an important research topic. Construction waste, such as fragments of lightweight bricks and concrete, can be recycled and used as aggregates in concrete mixtures. Previous studies have shown that utilizing such waste not only helps address environmental issues but can also enhance the compressive strength of concrete to a certain extent. This research aims to plan material requirements to achieve a concrete compressive strength of Fc' 20 MPa according to SNI 7656-2012, determine the compressive strength resulting from the use of a mixture of two types of construction waste (where concrete waste is substituted for coarse aggregate and hebel waste is substituted for fine aggregate) with substitution rates of 0%, 15%, and 30%, and analyze the effect of using construction waste on the compressive strength of concrete. The methodology used in this research is experimental. The results at 28 days show that the compressive strength for normal concrete with 0% construction waste substitution is 20.93 MPa, with 15% substitution is 21.30 MPa, and with 30% substitution is 18.94 MPa. Therefore, it can be concluded that concrete waste as a substitute for coarse aggregate and hebel waste as a substitute for fine aggregate with a 15% mixture can be used in normal concrete mixtures.